The Implementation of Group Investigation with Audio Visual Learning Media to Improve Student`s Learning Achievement and Student`s Attitude of Love the Homeland on Social Science Learning in Sambirejo 2 Junior High School - Andriati Rahayu; Sariyatun Sariyatun; Nunuk Suryani (Yupa: Historical Studies Journal, 2018)
The purpose of this research is to know the effectiveness of implementation of cooperative learning with group investigation and audiovisual media learning to improve student learning achievement and student`s attitude of love the homeland at junior high school students. The classroom action research was used as research approach. The subjects of research subjects were teachers and 32 students of class VIIIA. The data were analyzed by interactive analysis technique and comparative descriptive analysis. The results of this study indicate the improvement of learning achievement with an average value of 70 in cycles I, 77 in cycles II, and 81.75 in cycle III. Meanwhile the attitude score for love of the homeland shows improvement with the average yield of 72 in cycles I, 82 in cycles II, and 85 in cycle 3. Based on the results of the research, it can be concluded that the learning model for study Group Investigation with audiovisual learning media had proved to improve the learning achievement and attitude of love the homeland of student in the class VIIIA Sambirejo 2 State Junior High School.